“I Have Big, Big, BIG Dream!”: Realigning Instruction with the Language-Learning Needs of Adult Syrians with Refugee Experience in Canada - Huang, Li-Shih (Refuge: Canada's Journal on Refugees, 2021)
This article reports on a study involving multiple sources of data that captured adult Syrian refugee learners’ unique language-learning needs by developing and implementing needs assessment surveys; conducting in-depth, semi-structured interviews with the learners and teachers; and analyzing the learners’ oral production. The insights gained from the analysis of direct data (the learners’ oral production) and indirect data (content analysis using NVivo 12 Plus of the learning needs reported by learners and teachers) are intended to inform the work of researchers conducting needs assessment as well as the practices that are applicable within and beyond the Canadian context of instructors and material developers working with English-language learners who are refugees.